Emersive storytelling: An exploration of animation and the fourth wall as a tool for critical thinking. Issue 1 (1st December 2018) - Wijers, Eva
The term 'emersive storytelling' explores the positive effects of breaking the fourth wall and the special role of animation in doing so. The word 'emersive' is coined by the author of this article in order to discuss a method of storytelling in which the fictionality of the medium is acknowledged, derived from the verb 'to emerge': to come forth into view from concealment or obscurity. While immersive storytelling strives to totally engage the viewer, emersive storytelling acknowledges its own fiction and, thus, the inherent so-called 'fourth wall' (the fictional wall between the medium and the audience). This creates two effects: Brecht's distancing effect and, conversely, what the author calls a 'closeness effect'. Brecht's distancing effect addresses the conscious intellectual connection the audience makes with the medium when the fourth wall is broken. Contrastingly, and complimentarily, as the author argues, the closeness effect describes the empathy an audience feels for characters even if the suspension of disbelief is broken. Emersive storytelling demands active participation from the viewer and triggers critical thinking both about the message of the story and about the medium itself. Animation is a self-reflective medium and its ability to reveal its own unreality and use this as a storytelling tool makes it well-suited for emersive storytelling. Several short case studies within this article will support this idea. In the last section, the article briefly looks into the future; with ever-more realistic-looking virtual reality and the rise of artificial intelligence, it might seem as though the fourth wall is disappearing. However, emersive storytelling can create ther distance required for critical reflection and help us reason with our relationship to these technologies. The paradox of the fourth wall is not one to be solved by immersing the viewer further and further, but one to be embraced and put to use emersively.